The Implementation of Wayground Interactive Quiz-Based Learning Media on Students’ Interest in Learning Fiqh: A Quasi-Experimental Study at MTs Al-Mahrus Medan Deli - Muhammad Habibi Rangkuti; Hasan Matsum (Ali Institute of Research and Publication, 2026)
Fiqh learning at the Islamic junior secondary school level requires learning media that can support students’ attention and engagement, particularly when the subject matter is often perceived as normative. This study aimed to examine the difference in the improvement of students’ interest in learning Fiqh between those taught using Wayground interactive quiz-based learning media and those taught through conventional instruction. This research employed a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The sample consisted of 54 eighth-grade students at MTs Al-Mahrus Medan Deli, including 27 students in class VIII B as the experimental group and 27 students in class VIII A as the control group. The research instrument was a 20-item questionnaire measuring students’ interest in learning Fiqh, which was found to be reliable with a Cronbach’s Alpha value of 0.920. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Levene’s homogeneity test, and the Mann-Whitney U test. The results showed that the mean gain score of the experimental group was 13.33, while that of the control group was 3.22. The Mann-Whitney U test yielded an Asymp. Sig. value of < 0.001, indicating a significant difference in the improvement of students’ learning interest between the two groups. These findings suggest that Wayground can be used as a supporting learning medium to enhance students’ interest in learning Fiqh within the context of this study.